Proses Kreatif Grup Musik Ruhui Rahayu dalam Penciptaan Karya untuk Mengenalkan Budaya Lokal - M Fahrian Noor; Anik Juwariyah; Trisakti Trisakti; Muhammad Marwan (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The topic of this research is the creative process of the Ruhui Rahayu music group in creating songs because this group does not only play folk songs, but also creates folk songs such as Panting Songs and Banjar Songs which is very important to preserve the culture. The purpose of this research is to describe Ruhui Rahayu s creative process in creating songs. The research method used is descriptive qualitative data obtained from interviews and observations of Ruhui Rahayu s group and literacy studies on the theory of creativity. The results of the study found that in making his song works, Ruhui Rahayu went through 4 stages, namely having creative personal characteristics marked by the presence of an element of fluency or the ability to produce many songs quickly in a short time, then in the process of working he goes through the stages of preparation, incubation until the emergence of inspiration. or new ideas. Furthermore, through the Press stage or self-motivation to work. The fourth stage is the production of songs that can be enjoyed.